Increased cytoplasm viscosity hampers aggregate polar segregation in Escherichia coli. Issue 4 (17th November 2015) - Oliveira, Samuel M. D.; Neeli‐Venkata, Ramakanth; Goncalves, Nadia S. M.; Santinha, João A.; Martins, Leonardo; Tran, Huy; Mäkelä, Jarno; Gupta, Abhishekh; Barandas, Marilia; Häkkinen, Antti; Lloyd‐Price, Jason; Fonseca, José M.; et al.
Summary: In E scherichia coli, under optimal conditions, protein aggregates associated with cellular aging are excluded from midcell by the nucleoid. We study the functionality of this process under sub‐optimal temperatures from population and time lapse images of individual cells and aggregates and nucleoids within. We show that, as temperature decreases, aggregates become homogeneously distributed and uncorrelated with nucleoid size and location. We present evidence that this is due to increased cytoplasm viscosity, which weakens the anisotropy in aggregate displacements at the nucleoid borders that is responsible for their preference for polar localisation. Next, we show that in plasmolysed cells, which have increased cytoplasm viscosity, aggregates are also not preferentially located at the poles. Finally, we show that the inability of cells with increased viscosity to exclude aggregates from midcell results in enhanced aggregate concentration in between the nucleoids in cells close to dividing. This weakens the asymmetries in aggregate numbers between sister cells of subsequent generations required for rejuvenating cell lineages. We conclude that the process of exclusion of protein aggregates from midcell is not immune to stress conditions affecting the cytoplasm viscosity. The findings contribute to our understanding of E . coli 's internal organisation and functioning, and its fragility to stressful conditions. Abstract : In Escherichia coli, under optimal conditions, protein aggregates associated with cellular aging are excluded from midcell by the nucleoid. We show that this fails to occur under unfavourable conditions that increase cytoplasm viscosity (e.g. low temperatures and osmotic stress), because this weakens the anisotropies in aggregate dynamics at the nucleoid borders. Consequently, in the long‐term, aggregate numbers at midcell increase and asymmetries between sister cells in future generations decrease, hampering the rejuvenation of cell lineages.